2023
DOI: 10.1136/bmjopen-2023-071893
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute non-specific low back pain in the emergency department: do emergency physicians follow the guidelines? Results of a cross-sectional survey

Ilaria Jermini-Gianinazzi,
Manuel Blum,
Maria Trachsel
et al.

Abstract: ObjectivesClinical guidelines for acute non-specific low back pain (LBP) recommend avoiding imaging studies or invasive treatments and to advise patients to stay active. The aim of this study was to evaluate the management of acute non-specific LBP in the emergency departments (ED).SettingWe invited all department chiefs of Swiss EDs and their physician staff to participate in a web-based survey using two clinical case vignettes of patients with acute non-specific LBP presenting to an ED. In both cases, no neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The median ODI at day 7 in the control group was 13 (IQR, 5-19), whereas it was 11 (IQR, [6][7][8][9][10][11][12][13][14][15][16][17][18] in the intervention group (as demonstrated in Figure 3 and Table 2). The Wilcoxon test showed that the difference between the two groups was not significant (p = 0.854, effect size r = 0.0198 [95% CI 0.003 to 0.25]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median ODI at day 7 in the control group was 13 (IQR, 5-19), whereas it was 11 (IQR, [6][7][8][9][10][11][12][13][14][15][16][17][18] in the intervention group (as demonstrated in Figure 3 and Table 2). The Wilcoxon test showed that the difference between the two groups was not significant (p = 0.854, effect size r = 0.0198 [95% CI 0.003 to 0.25]).…”
Section: Resultsmentioning
confidence: 99%
“…As there are no specific guidelines for the management of nonspecific LBP in EDs, a wide variation in the management of these patients has been described [ 5 , 6 ]. However, guidelines originating in primary care could be applied to the ED setting [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While guidelines are slow to impact clinical practice in medicine, 22 , 23 ongoing research as well as dissemination of research evidence is crucial. Research into acupuncture effectiveness has moved from efficacy trials of very specific patient sets, using rote acupuncture prescriptions and non-inert sham acupuncture as a comparator 24 , 25 , 26 to more pragmatic trials: comparing acupuncture therapy to another therapy or usual care in a real-world settings with diverse real-world patients.…”
Section: Introductionmentioning
confidence: 99%